Pancasila as a Paradigm of Socio-Cultural Development - Putri, Dina Lutfiana (Indonesian Journal of Pancasila and Global Constitutionalism, 2023)
Currently, there are many cultures that deviate from the prevailing norms. Lots of people forget the values of Pancasila that already exist. The existence of western culture makes our nation forget the culture that we have ourselves. Some of them are even more proud when using the culture of other nations. As a result, the culture that we have is eroded and gradually lost by the times. It's not a bad thing if we know other cultures, but we must not forget the culture of our own country. But today, they actually forget the identity of their own country, the prevailing paradigm is gradually disappearing. Paradigm is a person's perspective that can influence a person's way of thinking (cognitive), behaving (affective) and behaving (conative). Paradigm itself is very influential on a person's behavior in implementing Pancasila values. If the values in Pancasila are practiced properly, of course we will not lose our own national identity. The existence of Pancasila is also a guideline for upholding noble human values. Pancasila itself is essentially humanistic because Pancasila is based on the position of human nature or what is commonly called human rights. As stated in the five precepts, Pancasila always puts human rights first. This is in accordance with what is stated in the second precept, namely Just and Civilized Humanity. Thus, socio-cultural development must uphold human values and human dignity in order to produce cultured and civilized human beings.